2021
DOI: 10.1002/hep4.1843
|View full text |Cite
|
Sign up to set email alerts
|

Covid‐19 and Liver Injury: Role of Inflammatory Endotheliopathy, Platelet Dysfunction, and Thrombosis

Abstract: Liver injury, characterized predominantly by elevated aspartate aminotransferase and alanine aminotransferase, is a common feature of coronavirus disease 2019 (COVID‐19) symptoms caused by severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2). Additionally, SARS‐CoV‐2 infection is associated with acute‐on‐chronic liver failure in patients with cirrhosis and has a notably elevated mortality in patients with alcohol‐related liver disease compared to other etiologies. Direct viral infection of the liver wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 156 publications
(194 reference statements)
0
45
0
3
Order By: Relevance
“…Acute dysregulations in hemostasis and inflammation are prominent features of patients with moderate-to-severe COVID-19 (3). Thrombi have been detected in the lung, heart, brain, and liver of COVID-19 patients, and the prevalence of deep vein thrombosis in hospitalized patients with an infection is significantly increased (4)(5)(6). Microthrombosis, also extensively documented by autopsy reports, reflects the increased platelet activation and subsequent fibrin clot formation in the pulmonary microvasculature in 80%-100% of lungs examined (7).…”
Section: Introductionmentioning
confidence: 99%
“…Acute dysregulations in hemostasis and inflammation are prominent features of patients with moderate-to-severe COVID-19 (3). Thrombi have been detected in the lung, heart, brain, and liver of COVID-19 patients, and the prevalence of deep vein thrombosis in hospitalized patients with an infection is significantly increased (4)(5)(6). Microthrombosis, also extensively documented by autopsy reports, reflects the increased platelet activation and subsequent fibrin clot formation in the pulmonary microvasculature in 80%-100% of lungs examined (7).…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] It has been reported that infection with coronavirus disease 2019 induces severe ALI and lacks effective treatment. [4] According to the World Health Organization, the incidence of ALI continues to increase due to drug abuse, the heavy use of pesticides, environmental pollution, and unhealthy lifestyle habits. [1][2][3] There are three potential outcomes to ALI: disease resolution, progression to chronic liver injury, and progression to acute liver failure.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it may facilitate cholestasis by repressing hepatobiliary excretory function and by promoting ductular proliferation 24 . A recent study demonstrated that IL-6 is probably the main cytokine orchestrating this inflammatory response leading to liver damage 50 . Specifically, high levels of interleukin-6 lead through IL-6 signaling to increased expression of procoagulants, proinflammatory factors [von Willebrand factor (vWF) and factor VIII], increased cell surface vWF and enhanced platelet attachment in liver sinusoidal endothelial cells, thus linking IL-6-mediated procoagulant endotheliopathy-endothelial inflammation with vascular inflammation and coagulation commonly observed in COVID-19 50 .…”
Section: Introductionmentioning
confidence: 99%